A strategy for test article selection and phytochemical characterization of Echinacea purpurea extract for safety testing. (March 2020) - Waidyanatha, Suramya; Pierfelice, Jessica; Cristy, Tim; Mutlu, Esra; Burback, Brian; Rider, Cynthia V.; Ryan, Kristen
Abstract: Botanical dietary supplements (BDS) are used around the world for many purported therapeutic properties. The selection of an authentic product and it's phytochemical characterization is critical to generate robust safety data. Because botanicals are complex mixtures with variable quality, identification of a representative product for testing has been challenging. Echinacea is used for its purported immune stimulant properties and was listed as the 2nd top-selling BDS in 2018. However, there are limited safety data for Echinacea. Hence, the National Toxicology Program (NTP) has selected Echinacea for safety testing using rodent models. Here, we describe selection and comprehensive characterization of an Echinacea purpurea root extract to be used in the NTP testing program. Using non-targeted chemical analyses combined with chemometric analysis, a potential unfinished product (i.e., an extract that serves as source material for finished products) of Echinacea purpurea was selected. The product was then authenticated using chemical and DNA techniques and characterized, including the phytochemical composition. Among numerous constituents identified, caftaric acid, chicoric acid, chlorogenic acid and dodeca-2(E), 4(E), 8(Z), 10(E/Z)-tetraenoic acid isobutylamide made up a small fraction of the extract. Based on these analyses, an approach is proposed for test article selection for Echinacea research which can be adapted to other botanicals. Highlights: Despite world-wide use of botanical dietary supplements, safety data are limited. Echinacea is used for its purported immune stimulant properties. This work describes selection and characterization of Echinacea product for testing. Various products were screened using non-targeted analysis and chemometric methods. The selected product was comprehensively characterized using multiple methods.